Translation and Validity Content Testing of The Quality Clincial Placement Evaluation Instrument - Ilfanty, Ananda Rafa; Yusanti, Irma; Anna, Anastasia (Universitas Padjadjaran, 2025)
Clinical learning environments are fundamental to nursing education, and their quality must be systematically evaluated. The Quality Clinical Placement Evaluation (QCPE) instrument is widely used to assess clinical placements; however, an Indonesian version has not been previously available. This study aimed to translate, culturally adapt, and assess the content validity of the QCPE instrument in the Indonesian context. A methodological study was conducted using a structured translation process comprising forward translation, synthesis, backward translation, and developer review to ensure conceptual equivalence. Content validity was evaluated by three Nursing Professional Practice experts who assessed each item for relevance, clarity, and essentiality. Quantitative analysis was performed using the Item Content Validity Index (I-CVI), Scale Content Validity Index (S-CVI/UA and S-CVI/Ave), and Content Validity Ratio (CVR). The Indonesian QCPE demonstrated good content validity. Most items achieved an I-CVI of 1.00, indicating high relevance. S-CVI/ UA values ranged from 0.82 to 0.95, and S-CVI/Ave values ranged from 0.94 to 0.98, reflecting strong overall agreement among experts. CVR values ranged from 0.33 to 1.00. One item from each questionnaire was removed due to limited relevance to the Indonesian nursing education context, resulting in a final version with 20 items for the Professional Student Questionnaire and 16 items for the Supervisory Nurse Questionnaire. The Indonesian version of the QCPE instrument demonstrates strong content validity and is suitable for evaluating clinical learning environments. Further studies are recommended to establish construct validity and reliability prior to widespread use.Keywords: Content Validity, Clinical Learning Environment, Cross-Cultural Adaptation, Nursing Education